TRANSFORMASI DIGITAL DI MADRASAH IBTIDAIYAH DI KOTA BANDA ACEH DAN KABUPATEN ACEH BARAT - Jamin, Hanifuddin; Rohman, Nur (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2025)
Abstract This study aims to analyze the acceleration of digital transformation in Madrasah Ibtidaiyah in Aceh Province through digital madrasah program management. This study uses a qualitative descriptive methodology, where data is collected through observation, interviews, and documentation from several madrasas. The focus of the research is to identify the availability of digital facilities such as projectors, laptops, computers, internet networks, and the Jelajah Ilmu digital platform, as well as to map the level of utilization and implementation of these facilities in the learning process. The results of the study show that all madrasas have adequate digital facilities, but there are differences in terms of their use. The two madrasas identified as the most superior in the implementation of digital transformation are MIN 6 Banda Aceh City and MIM 9 Banda Aceh City. In conclusion, although digital infrastructure is available in all madrasas, the effectiveness of its utilization still requires improved program management to optimize digital transformation across madrasas. Keywords: : digital transformation, madrasah ibtidaiyah, program management